Hubungan Pengetahuan Ibu dan Sikap Anak terhadap Kelengkapan Imunisasi Lanjutan di Sekolah Dasar Negeri Surabaya - Nisrina Nadia Rachmadicha; Siti Nuhaida; Alfi Nur Fauzia; Humaira Izka Alfatihah; Nada Firdaus; Putri Diana Yusuf; Qory Pramita; Karunia Nurul Fatihah; Fauziah Nur Fadila; Nabila Zalfadania; Ade Ayu Sukma Puspita Putri; Gusti Noorzka Veronika Akhmad (Jurnal Farmasi Komunitas, 2022)
Immunization is an effort to actively increase a person's immunity against a disease. The purpose of immunization is to decrease the number of illness, disability, and deaths from diseases that can be prevented by immunization. One of the immunization programs of the Indonesian Ministry of Health is advanced immunization given to children under two years old, elementary school students, and women of childbearing age. Until 2017, cases of diphtheria were reported, which was quite high because of the low immunization coverage. This study aims to determine the relationship between maternal knowledge and children's attitudes with the completeness of advanced immunization in elementary school students in one of the public elementary schools in Tanah Kali Kedinding, Surabaya City. This research used an analytical study with a cross sectional approach. The sampling method chosen was stratified random sampling with data collection technique using a questionnaire as the instrument. The questionnaire consisted of 15 multiple choice questions with one correct answer for each knowledge category question, and 7 statements for the attitude category with a Likert scale. A total of 220 respondents agreed to participate in this study. The collected data were analyzed using the Spearman rank correlation test. The results showed that maternal knowledge influenced the completeness of advanced immunization, meanwhile there was no connection between children's attitudes and completeness of advanced immunization.